HUBUNGAN KEPUASAN PASIEN TERHADAP DAMPAK PELAYANAN BPJS KESEHATAN DI PUSKESMAS AIK MUAL KABUPATEN LOMBOK TENGAH PADA TAHUN 2024 - Ardini, Aufa; Lale Ajeng Khalifatun Wardani; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Fathurrahman; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2024)
Patient perceptions about the impact of BPJS health services with a good category of 89 people (89%) while the category is not good as many as 11 people (11%). Patient perceptions about patient satisfaction who feel satisfied as many as 95 people (95%) while those who feel dissatisfied as many as 5 people (5%). Based on the results of statistical tests obtained p value (Asymptotic Significance) Pearson Chi Square = 0.033 <α 0.05 (Significant) which means there is a significant relationship between patient satisfaction with the impact of BPJS health services at the Aik Mual Community Health Center, Central Lombok Regency. This means that the quality of environmental cleanliness factors will affect patient comfort, the better the quality of environmental cleanliness of the Community Health Center, the more comfortable the patient feels.